Insecurity and tourism SME performance in Jos Metropolis: Evidence from a mixed-methods analysis - Kwon-Ndung, Emmanuella; Akande, Olumuyiwa A. (Journal of Commerce, Management, and Tourism Studies, 2026)
Tourism-dependent businesses and small- and medium-sized enterprises (SMEs) in emerging destinations are highly vulnerable to insecurity. This study quantifies the effects of insecurity-related mechanisms on business income among tourism-related businesses in Jos Metropolis, Plateau State, using primary field data collected in 2025. A cross-sectional survey of tourism and hospitality operators and proprietors of tourism-related businesses was analyzed using multiple linear regression. Predictor variables captured insecurity pathways: decline in customer patronage, perceived seriousness of insecurity, business disruptions, effects on investment and expansion, government support, and adoption of business innovations. Semi-structured interviews with stakeholders triangulated quantitative findings. Results showed the model explaining 16.4% of the variation in business income (R² = 0.164) and was statistically significant (F = 5.236, p < 0.05). Decline in customer patronage due to insecurity was the only statistically significant predictor of income loss (B = 0.357; Beta = 0.354; t = 4.856; p < 0.001). Other predictors were not significant. Qualitative evidence indicates that visible security incidents, negative media coverage, and travel advisories reduce visitor flows and directly depress revenues for hotels, restaurants, transport operators, event centers, and recreational facilities. Tourism-related businesses adopt coping strategies that mitigate immediate losses but do not restore lost tourist demand. It can be concluded that sustained insecurity undermines tourism-related businesses’ viability primarily through reduced patronage. Policy responses must prioritize targeted security improvements, accessible institutional support, and coordinated destination-image restoration paired with market-access innovations for the businesses.